A study on the application of LIS information technology subjects in BLIS graduates' work and job opportunities - Mendoza, Adeo Cyrus R. (2008)
The developments in technology have made great impacts in the field of Librarianship. Information today comes in a wide variety of formats with different means of storage and retrieval. That is why Librarians and Information Professionals are now obliged to educate themselves with IT in order to face the current demands of the clientele. It is in this light that this study focused on the application of LIS Information Technology subjects in the work of graduates of Bachelor of Library and Information Science.